2018
DOI: 10.31616/asj.2018.12.6.1106
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Modified Disability Questionnaire for Evaluating Disability Caused by Backache in India and Other Developing Countries

Abstract: Study DesignProspective observational study.PurposeTo evaluate the disability domains relevant to Indian patients with low backache and propose a modified disability questionnaire for such patients.Overview of LiteratureThe Oswestry Disability Index (ODI) is a self-reported measurement tool that measures both pain and functional status and is used for evaluating disability caused by lower backache. Although ODI remains a good tool for disability assessment, from the Indian perspective questions related to weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Among these aspects, there were questions related to mental health, suicide, and sexual life. This is in line with Aithala et al [30] who in their Indian study found that 56.8% of the patients did not answer the questions related to sexual activity. While some of our interviewees expressed a preference for talking about mental problems with members of the healthcare staff, others said they only would discuss such questions with close family member.…”
Section: Patient Experiences From Filling In Promssupporting
confidence: 90%
“…Among these aspects, there were questions related to mental health, suicide, and sexual life. This is in line with Aithala et al [30] who in their Indian study found that 56.8% of the patients did not answer the questions related to sexual activity. While some of our interviewees expressed a preference for talking about mental problems with members of the healthcare staff, others said they only would discuss such questions with close family member.…”
Section: Patient Experiences From Filling In Promssupporting
confidence: 90%
“…The determined amputation-specific PROMs were tailored toward patients with LEA who use socket- or bone-anchored prostheses and included the Orthotics and Prosthetics User's Survey (OPUS-LEFS) 19 , Prosthesis Evaluation Questionnaire (PEQ) 20 , Trinity Amputation and Prosthesis Experiences Scales (TAPES) 21 , Questionnaire for Persons with a Transfemoral Amputation (Q-TFA) 22 , Prosthetic limb users survey of Mobility (PLUS-M) 23 , Special Interest Group in Amputee Medicine (SIGAM) 24 , Groningen Questionnaire Problems Leg Amputation (GQPLA) 25 , Houghton Scale (HS) 26 , Satisfaction with Prosthesis Questionnaire (SATPRO) 27 , Locomotor Capabilities Index (LCI-5) 28 , Prosthetic Profile of the Amputee (PPA) 29 , Day's Amputee Activity Survey (AAS) 30 , Attitude to Artificial Limb Questionnaire (AALQ) 31 , and the Amputee Body Image Scale (ABIS) 32 . The health-related QoL PROMs included the 36-Short Form (36-SF) 33 , Patient-Reported Outcomes Measurement Information System-Global Health 10 items (PROMIS-GH) 34 , European Quality of Life (EQ-5D-3L) 35 , World Health Organization Quality of Life Assessment Instrument 2.0 (WHO-DAS 2.0) 36 , Modified Oswestry Disability Index (MODQ) 37 , American Academy of Orthopedic Surgeons-Lower Limb Questionnaire (AAOS-LLQ) 38 , LIMB-Q 39 , Functional Assessment Interview (FAI) 40 , Functional Assessment Measure (FAM) 41 , Functional Independence Measure (FIM) 42 , Limb Deformity Modified Scoliosis Research Society (LD-SRS) 43 , Activities-specific Balance Confidence (ABC) Scale 44 , Locomotor Capabilities Index (LCI-5) 28 , Engagement in everyday activities involving revealing the body (EEARB) 45 , International Physical Activity Questionnaire (IPAQ)—Short Form 46 , Multidimensional Body-Self Relations Questionnaire Appearance Evaluation subscale (MBSRQ-AE) 47 , Reintegration to Normal Living Index (RNLI) 48 , Nottingham Health Profile (NHP) 49 , and Functional Independence Measure (FIM) 42 . The Single Assessment Numeric Evaluation (SANE), visual analog scale (VAS), and Numeric Rating Scale (NRS) of pain were excluded because they consisted of only a single number (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The secondary outcome involved assessing changes in disability, measured by the Oswestry Disability Index (ODI) [15], Modified Oswestry Disability Index (MODI) [16], Quebec Back Pain Disability Scale (QBPDS) [17], Roload Morris Disability Questionnaire (RMDQ) [18], 36-Item Short Form Survey (SF-36) [19], and 12-Item Short Form Survey (SF-12). Elaborate explanations are systematically arranged in Table S3 to enhance clarity.…”
Section: Secondary Outcome Measurementsmentioning
confidence: 99%